Assessing the relationship between obesity and asthma in adolescent patients: a review - Ross KR; Hart MA (Dove Medical Press, 2013)
Kristie R Ross, Meeghan A HartDepartment of Pediatrics, Rainbow Babies and Children's Hospital and Case Western Reserve University School of Medicine, Cleveland, OH, USAAbstract: The parallel rise in the prevalence of obesity and asthma over the last several decades has led to an extensive line of investigation into the relationship between these two conditions. This review will discuss evidence from laboratory-based studies, observational clinical studies, and clinical trials that suggests that obesity adversely influences asthma through multiple mechanisms. The effect of obesity on asthma during adolescence, including asthma incidence, the severity and control of existing asthma, lung function, and exacerbations, will be reviewed.Keywords: children, airway reactivity